Multiporous Nanofibers of SnO2 by Electrospinning for High Efficiency Dye-Sensitized Solar Cells - Fakharuddin, Azhar; Wali, Qamar; Irfan, Ahmed; Mohd Hasbi, Ab. Rahim; Jamil, Ismail; Rajan, Jose (Royal Society of Chemistry, 2014)
Various one-dimensional nano-morphologies, such as multiporous nanofibers (MPNFs), porous nanofibers (PNFs), and nanowires (NWs) of SnO2, are synthesized using electrospinning technique by controlling the tin precursor concentration. The MPNFs have [similar]8-fold higher surface area compared to the other morphologies. Dye-sensitized solar cells (DSCs) were fabricated using these nanostructures as photoanodes and their performance was compared. The MPNFs surpass the performance of PNFs and NWs as well as conventional TiO2 paste. Record photoconversion efficiency (PCE) of [similar]7.4% was realized in MPNFs DSCs, which was twice to that achieved using PNFs ([similar]3.5%). Furthermore, the MPNFs showed over >80% incident photon to current conversion efficiency (22% higher than that achieved by spherical P25 TiO2 particles) and also demonstrated [similar]3 times longer electron lifetime and electron diffusion length. Owing to the possibility to produce large quantities using electrospinning technique, huge commercial potential of SnO2 nanostructures, and promising results achieved herein, the MPNFs are expected soon to be utilized in commercial devices.